The Causality Relationship between Economic Growth and Energy Consumption in The World's top Energy Consumers - Almozaini, Majed S. (International Journal of Energy Economics and Policy, 2019)
The purpose of this paper is to empirically and economically investigate the causal relationship between economic growth and energy consumption in five countries with high consumption during the period of 1968-2016. These countries are China, India, Japan, the United States, and Saudi Arabia. Using the cointegration relationship between the variables procedure and the Granger causality test. This period witnessed various changes in the economy, consumption, and production of these countries. The causality results for the countries show that there is a unidirectional, and bidirectional Granger causality between the variables. Therefore, the energy conservation policy should be designed with caution, as energy is an engine for GDP growth. Keywords: energy consumption, economic growth, Granger causality JEL Classifications: C20; Q43; C32 DOI: https://doi.org/10.32479/ijeep.7657